The values of x = -6 and y = 6 satisfy both the equations; therefore, (-6, 6) is the solution. The correct option is a)
From the question, we are to determine the solution of the given system of equations
The given system of equations are
2 x + 3 y = 6 ------- (1)
x + 3 y = 12 ------- (2)
From equation (2)
x + 3y = 12
Then, we can write that
x = 12 - 3y --------- (3)
Substitute this into equation (1)
2x + 3y = 6
2(12 -3y) + 3y = 6
24 - 6y + 3y = 6
24 -3y = 6
24 - 6 = 3y
18 = 3y
∴ y = 18/3
y = 6
Substitute the value of y into equation (3) to get the value of x
x = 12 - 3y
x = 12 -3(6)
x = 12 - 18
x = -6
∴ x= -6 and y = 6 ; Thus, (-6, 6) is a solution
Hence, the values of x = -6 and y = 6 satisfy both the equations; therefore, (-6, 6) is the solution. The correct option is a)
Learn more on Simultaneous linear equations here: https://brainly.com/question/16863577
#SPJ1